Repeatability and Agreement of Central Vault for Implantable Collamer Lens Obtained by the Tomey OA-2000 Biometer and Spectralis OCT - Hao Wu; Zuocheng Wang; Pengfei Wang; Yifei Meng; Zengying Wang; Yuhong Xue; Bohua Jiang; Shuaixi Pan; Zhipeng Yan (Journal of Ophthalmology)
Objective. To assess repeatability and agreement of central vault for implantable collamer lens (ICL) measured by the Tomey OA-2000 biometry and Spectralis optical coherence tomography (OCT). Methods. In this prospective study, the central vault was measured by the Tomey OA-2000 biometer and Spectralis OCT in 84 eyes (43 patients) after ICL implantation at six month follow-up. Three consecutive scans were obtained by one experienced technician using Tomey OA-2000 and the Spectralis OCT in the same day. The coefficient of variation (CoV), intraclass correlation coefficient (ICC), within-subject standard deviation (Sw), and 2.77 Sw were calculated to assess the repeatability and reproducibility. The paired t-test and Bland–Altman plots were used to analyze the differences and agreements of central vault measured by two devices. Results. Repeatability of the central vault measured by Tomey OA-2000 biometer and Spectralis OCT showed that the CoV was 2.71% and 1.66%, respectively. The ICC for both devices was 0.996 and 0.999, respectively. The paired t-test showed that central vault measured by Tomey OA-2000 biometer was −7.25 ± 23.57 microns lower than that measured by Spectralis OCT (P=0.006). The mean difference between measurements for Tomey OA-2000 and ASM-OCT with 95% limits of agreement (LoAs) was −38.94 to 53.44 μm. Conclusion. Both Tomey OA-2000 biometer and Spectralis OCT displayed good repeatability for the measurement of central vault of ICL. Good reliability and agreement were observed between Tomey OA-2000 biometer and Spectralis OCT. Both instruments are useful but not replaced each other for central vault measurements.